2014
DOI: 10.4172/2155-9546.1000205
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chankanay Zeolites as Feed Additives on the Chemical, Biochemical and Histological Profile of the Rainbow Trout (Oncorhynchus mykiss)

Abstract: This article presents the results of the influence of zeolites as feed additives on the chemical, biochemical and histological profile of fish. Research was conducted for 63 days using a rainbow trout from Turgen village (Kazakhstan). The studied material was zeolitic tuff from the Chankanay deposit as an additive to RGM-2M feed. The fish were fed with a normal diet, and the diet supplemented with 1%, 2%, 3% and 4% of natural zeolites. Pathomorphological and histological examinations of muscle tissues and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…A zeolite-rich tuff was successfully used as a supplement to the diet of carp fingerlings (Polyakov et al 2009a). Adding a natural zeolite from the Chankanay deposit (Kazakhstan, Almaty region) into the diet of rainbow trout in the amount of 1-4% weight of the diet showed that zeolite is a valuable feed additive with natural origin that promotes the production of the fish meat both qualitatively and quantitatively (Paritova et al 2013). It has also been suggested that zeolitic products can be used as part of the medium to improve the nutritional quality of the marine diatom Thalassiosira weissflogii (Grunow) (Arredondo-Vega et al 2004).…”
Section: Zeolites As Feed Additive To Improve Fish Growth and Healthmentioning
confidence: 99%
“…A zeolite-rich tuff was successfully used as a supplement to the diet of carp fingerlings (Polyakov et al 2009a). Adding a natural zeolite from the Chankanay deposit (Kazakhstan, Almaty region) into the diet of rainbow trout in the amount of 1-4% weight of the diet showed that zeolite is a valuable feed additive with natural origin that promotes the production of the fish meat both qualitatively and quantitatively (Paritova et al 2013). It has also been suggested that zeolitic products can be used as part of the medium to improve the nutritional quality of the marine diatom Thalassiosira weissflogii (Grunow) (Arredondo-Vega et al 2004).…”
Section: Zeolites As Feed Additive To Improve Fish Growth and Healthmentioning
confidence: 99%
“…Studies have demonstrated that use of zeolites in fish culture has shown a significant positive effect on fish that consume them, similar to the addition of antibiotics. Zeolites also have the ability to decrease ammonia levels, which could be very toxic for fish, and can lead to decreased growth, even in small concentrations 30…”
Section: Discussionmentioning
confidence: 99%
“…Жaлпы, aғзaдa әртүрлі пaтологиялық үрдіcтeрдің дaмуы caлдaрынaн рН көрceткішінің мәні қышқылғa нeмece cілтіліккe aуыcуы бaйқaлaды. РН нормaдaн aуытқығaн кeздe фeрмeнттeрдің бeлceнділігі eдәуір төмeндeйді, aл бұл өз кeзeгіндe жacушaлaрдың қырылуынa әкeлeді [12]. Кecтeдeгі aлынғaн мәлімeттeргe cәйкec eкі топтaғы бaлық eтінің рН мөлшeрі 6,6дaн 6,7-гe дeйін болғaнын көругe болaды.…”
Section: сурет -бAлықтaрды оргAнолeптикaлық зEрттeуunclassified